Molecular triaging options for women testing HPV positive with self-collected samples - Taghavi, Katayoun; Zhao, Fanghui; Downham, Laura; Baena, Armando; Basu, Partha (Frontiers in Oncology, 2023)
We review developments in molecular triaging options for women who test positive for high-risk human papillomavirus (hrHPV) on self-collected samples in the context of cervical cancer elimination. The World Health Organization (WHO) recommends hrHPV screening as the primary test for cervical screening due to its high sensitivity compared to other screening tests. However, when hrHPV testing is used alone for treatment decisions, a proportion of women of childbearing age receive unnecessary treatments. This provides the incentive to optimize screening regimes to minimize the risk of overtreatment in women of reproductive age. Molecular biomarkers can potentially enhance the accuracy and efficiency of screening and triage. HrHPV testing is currently the only screening test that allows triage with molecular methods using the same sample. Advancements in molecular triaging can enhance the accuracy and efficiency of screening women for high-risk human papillomavirus (hrHPV) to eliminate cervical cancer. Adding a triage test to hrHPV screening could improve its positive predictive value (PPV) and reduce overtreatment. Molecular methods like genotyping, methylation tests, and detection of HPV viral load in the same sample can improve the prediction of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) and invasive cancer. Self-collected hrHPV tests can increase screening coverage, but more research is needed to determine their effectiveness and cost-efficiency for diverse populations. Molecular triaging options offer promising alternatives to traditional methods and can help achieve the global goal of eliminating cervical cancer as a public health problem.